Effects of endurance exercise and Urtica dioica on the functional, histological and molecular aspects of the hippocampus in STZ-Induced diabetic rats. (28th June 2020) - Keshvari, Maryam; Rahmati, Masoud; Mirnasouri, Rahim; Chehelcheraghi, Farzaneh
Abstract: Ethnopharmacological relevance: Many body systems and organs, including the hippocampus, are affected by diabetes, and undergo changes that may increase the risk of cognitive decline. Urtica dioica (UD) has long been recognized as a medicinal plant with beneficial effects on blood glucose control in diabetes. Aim of the study: The present study aimed to investigate the effect of endurance exercise (Ex), along with Urtica dioica (UD) hydro-alcoholic extract on some functional, histological, and molecular aspects of the hippocampus in streptozotocin (STZ)-induced diabetic rats. Materials and methods: 60 male Wistar rats were divided into five groups (N = 12): healthy control (H-C), diabetes control (D-C), diabetes exercise (D-Ex), diabetes Urtica dioica (D-UD), and diabetes exercise Urtica dioica (D-Ex-UD). Diabetes was induced intraperitoneally by STZ (45 mg/kg) injection. Two weeks after the injection by STZ, Ex (moderate intensity/5day/week) and gavage of UD extract (50mg/kg/day) was performed for six weeks. Cognitive functions were evaluated by the Morris Water Maze test, routine histological examination, and molecular studies were done via Hematoxylin & Eosin stain, and Western blot. Results: Diabetic rats showed spatial learning and memory deficits, as well as negatively affects to the tissue and structure of the hippocampus in the dentate gyrus (DG) and cornu ammonis (CA) areas. Ex + UD treatment caused a decrease of neural disorganization, an increase of neural-microglial density, and thickness of the pyramidal-molecular layer in the hippocampus. In addition, Ex + UD caused a rise of GAP-43 protein levels, a reduction of CAP-1 protein levels, improved hippocampal structure, and improved learning and memory function. Conclusions: These results show that Ex, along with the UD extract, may decrease levels of the central neural complications of diabetes. Given the importance of recognizing non-pharmacological complementary therapies in this field, future studies are warranted. Graphical abstract: Image 1